Expression and purification of the truncated duck DTMUV NS5 protein and the subcellular localization of NS5 in vitro. (27th March 2019) - Duan, Yanping; Zeng, Miao; Zhang, Wei; Liu, Peng; Yang, Chao; Wang, Mingshu; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Yang, Qiao; Wu, Ying; Zhao, Xinxin; et al.
ABSTRACT: Duck Tembusu virus (DTMUV) non-structural protein 5 (NS5), which harbors an N-terminal methyltransferase (MTase) domain and a C-terminal RNA-dependent RNA polymerase (RdRp) domain, is central to virus replication. In this study, a sequence encoding amino acid residues 1–408 of NS5 was amplified and ligated into a pET32a vector to generate a pET32a-NS51-408 expression vector. Recombinant protein was expressed, purified, and used to arise a mouse anti-NS5 specific polyclonal antibody (DTMUV-NS51-408 mPAb). Indirect immunofluorescence assays indicated that NS5 protein localized within the cytoplasmic region of DTMUV-infected or transfected cells; the localization was not affected in the presence of a nuclear export inhibitor. This study provides the first demonstration that, in contrast to the data reported for NS5 proteins of Dengue and Yellow fever virus, DTMUV NS5 had slight nuclear localization activity.